2022
DOI: 10.17269/s41997-022-00692-y
|View full text |Cite|
|
Sign up to set email alerts
|

Oral healthcare disparities in Canada: filling in the gaps

Abstract: As a key component of overall health and quality of life, oral health is recognized by public health organizations globally as a basic human right. Dentists are oral health experts involved in the primary prevention of oral injury and the detection and management of oral diseases. As regulated healthcare professionals, dentists identify and treat dental caries, gum disease, oral cancers, and edentulism, among other conditions. Oral diseases that go undetected and/or untreated burden patients with increased sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…The SEM analysis also showed that expenses for oral disease per year influenced attitudes. Indeed, several studies showed that treatment costs were a barrier to proper oral health ( 37 , 38 ). In the present study, two-thirds of the participants were ≤35 years old.…”
Section: Discussionmentioning
confidence: 99%
“…The SEM analysis also showed that expenses for oral disease per year influenced attitudes. Indeed, several studies showed that treatment costs were a barrier to proper oral health ( 37 , 38 ). In the present study, two-thirds of the participants were ≤35 years old.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is well documented that populations living in areas geographically distant from the health system and/or with low health literacy and/or low economic status are particularly prone to poor health conditions [ 16–18 ]. Such populations are also more affected by caries than the rest of the population of the countries where they live due to a cultural gap and a lack of impact of adapted prevention policies [ 19 ].…”
Section: Introductionmentioning
confidence: 99%